Design and Validation of an Understanding by Design-Based Science Assessment Module for Secondary Schools under Indonesia’s Merdeka Curriculum (Jurnal Pendidikan Fisika, 2026)
Assessment practices in secondary science and physics classrooms often emphasize scoring rather than generating actionable evidence of students’ understanding. This challenge becomes more urgent under the Merdeka Curriculum, which positions assessment as an integral component of learning. To address this need, this study aimed to develop and validate a teacher guide module for UbD (Understanding by Design)-based science assessment for junior and senior secondary levels by operationalizing backward design and the six facets of understanding into practical procedures, templates, and worked examples. Using a research and development approach with the 4D model (Define–Design–Develop–Disseminate), the module was produced through needs analysis, curriculum and literature review, and iterative drafting. Content validation was conducted by three validators using a four-point relevance scale, analyzed with feasibility percentages and Aiken’s V complemented by Score (Wilson) confidence intervals. Practicality was examined through a limited pilot involving three science teachers who applied the module and completed a five-point response questionnaire. The results showed high feasibility across usefulness, practicality, conceptual accuracy, and language/visual design. At the same time, item-level content validity was strong (Aiken’s V = 0.78–1.00) with conservative lower confidence bounds indicating at least moderate validity for all items. Teachers reported uniformly positive perceptions, with perceived usefulness rated highest (M = 4.83), although implementation of the Explanation facet was relatively more challenging (lowest item mean, M = 3.67). This study’s novelty lies in providing a step-by-step, facet-based assessment design guide that explicitly links learning objectives, acceptable evidence, and analytic rubrics within a single teacher-ready resource. In conclusion, the validated module is feasible and practically promising as an evidence-centered tool to strengthen alignment between curriculum outcomes and assessment in secondary science. The module contributes to physics education by supporting teachers to design authentic, rubric-based assessments that better capture students’ scientific reasoning and conceptual understanding.
Keywords: backward design; merdeka curriculum; module; science assessment; understanding by design